The relationship between digital game addiction tendency and body image in preschool children - Oğraş, Berfin; Kale, Mustafa; Özpoyraz, Nurgül (Journal of Dependence, 2025)
Objective: This study aims to examine the relationship between body image and digital game addiction tendency in preschool children aged 4-6, as well as how this relationship varies according to demographic variables such as age, gender, and parental education and employment status. Method: The study was conducted using a relational survey model based on the quantitative research method. The study included 116 preschool children living in Adana and Mersin. Children’s body image was assessed using the Body Image Silhouette Test, while digital game addiction tendency was measured using the Digital Game Addiction Tendency Scale, which includes the subscales "disconnect from life," "conflict," "continuous play," and "reflection in life." Results: The analysis results indicated a low-level positive and significant relationship between the total score of digital game addiction tendencies and children’s body image. Specifically, the sub-dimensions of "reflection on life" and "continuous play" showed a low-level positive and significant relationship with body image. Additionally, it was determined that digital game addiction tendencies exhibited significant differences based on demographic variables. Conclusion: The findings of the study demonstrate the presence of a relationship between digital game addiction tendencies and body image in children. It is recommended to increase awareness regarding the concepts of digital game use and body image and to replicate the study with larger sample groups and different variables.